Modeling actions for transforming agrifood systems - Laborde Debucquet, David; Torero, Maximo (Springer, 2023)
We modeled six interventions to study the scenarios’ impact on agrifood systems, undernutrition, access to healthy diets, and the environment. We also assessed the interventions as a group to consider the impact of synergies and complementarities. Our baseline showed that 690 million people were undernourished, and 3 billion people could not afford healthy diets in 2019. The first finding confirmed that ending chronic hunger at a 5% level by 2030 is possible, with key structural interventions to ramp up agrifood systems’ efficiency. Through increased farm productivity and reduction of food loss and waste, the number of chronically hungry people could be cut by 314 million. In addition, 568 million people would be able to afford healthy diets by 2030. The cost of ending hunger represents 8% of the size of global food markets, a sum that can be mobilized and invested to generate impact through food value chains, national economies, and social safety nets. Furthermore, the use of well-targeted social safety nets could provide an additional 2.4 billion people with access to healthy diets. The second critical finding was that various interventions could create synergies. This would become apparent through addressing different causes of hunger. Moreover, aiming to minimize the total cost of interventions and seeking, at the same time, the highest return interventions in terms of reduction of undernourishment and an increase in access to healthy diets could create significant trade-offs in regard to sustainability. Countries would have to redistribute $1.4 trillion annually to fill the income gap of the 3 billion people who cannot afford healthy diets. However, by investing in various interventions, countries can drive down the cost of their safety nets by about two thirds or $428 billion globally, in 2030. Combined interventions can also address environmental trade-offs that are bound to occur.